Hypovitaminosis D in Healthy Health Care Professionals: A Real Deficiency or Necessity of New Reference Value for Specific Population? - Bhatta, Rajendra Dev; Pradhan, Nikita; Gurung, Rojeena; Risal, Prabodh (Journal of Lumbini Medical College, 2018)
Introduction: Vitamin D, a steroid vitamin, has attracted noticeable interest of clinicians and researchers for decades because of its diverse array of biological functions. Various studies have shown that the level of vitamin D is low in significant proportion of healthy individuals. However, indoor workers especially health care professionals are not focused, particularly in Nepal. We aimed to measure level of vitamin D in apparently healthy health care professionals. Methods: A descriptive cross-sectional study was carried out in apparently healthy health care professionals working at Kathmandu University Hospital in Dhulikhel, Nepal. Structured questionnaire including sociodemographics, dietary habits, and anthropometric measurements was filled in by the participants. Total serum 25-hydroxy vitamin D was measured by Chemiluminescence Immunoassay (CLIA) technique. Results were analyzed with t-test, Chi-square test, and Pearson correlation test. Results: Data from 64 female and 47 male were analyzed, mean 25-hydroxy vitamin D level was 8.81 ng/dl (SD = 4). Almost all (98.2%, n = 109) participants had vitamin D lower than normal where 72.7% (n = 92) were deficient, 24.5% (n = 17) were insufficient, and only 2.7% (n = 2) were having adequate level. Non-specific body pain was the only factor among all we studied that was significantly associated with vitamin D levels (p = 0.002). Conclusion: Hypovitaminosis of 25-hydroxy vitamin D was found to be very common (98.2%) in apparently healthy health care subjects of Dhulikhel Hospital. This may necessitate further research to redefine the biological reference value for our population. DOI: https://doi.org/10.22502/jlmc.v6i1.173